2015
DOI: 10.1007/s40135-014-0060-6
|View full text |Cite
|
Sign up to set email alerts
|

Presbyopic PiXL Cross-Linking

Abstract: We describe principles and initial clinical findings regarding a novel application of topographically customized collagen cross-linking (CXL) aiming to achieve a modest, nevertheless predictable hyperopic and presbyopic refractive changes. CXL is implemented in a specific, annular section mid-peripherally, employing differential response and biomechanical change, inducing central corneal steepening and asphericity changes. Efficacy, safety, and predictability of this procedure are also presented. This non-lase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 51 publications
1
2
0
Order By: Relevance
“…Moreover, we also consulted other literature to find the parameter values of normal and diseased mice, as the reference indexes in our work [37–39]. The reference values of the human eye listed in Table 3 were found in the studies of measuring eye structure in OCT images [40–42]. Observing these data, it can be concluded that, compared with the uncorrected images, the corrected data are reasonable and closer to the reference value, verifying the effectiveness of our proposed correction algorithms.…”
Section: Resultssupporting
confidence: 55%
“…Moreover, we also consulted other literature to find the parameter values of normal and diseased mice, as the reference indexes in our work [37–39]. The reference values of the human eye listed in Table 3 were found in the studies of measuring eye structure in OCT images [40–42]. Observing these data, it can be concluded that, compared with the uncorrected images, the corrected data are reasonable and closer to the reference value, verifying the effectiveness of our proposed correction algorithms.…”
Section: Resultssupporting
confidence: 55%
“… 7 , 22 , 26 29 Corneal approaches using an excimer laser include monovision, modification of corneal asphericity, and methods inducing corneal multifocality. 2 , 3 , 30 36 …”
Section: Discussionmentioning
confidence: 99%
“…CXL was implemented in a specific, annular section mid-peripherally, employing differential response and biomechanical change, inducing central corneal steepening and asphericity changes. 2 , 3 …”
Section: Discussionmentioning
confidence: 99%